ANALYSIS OF THE CURRENT STATE AND PROSPECTS OF HOTEL INDUSTRY DEVELOPMENT IN KHARKIV (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article conducts a comprehensive study of the current state and prospects of development of the hotel industry in Kharkiv in the context of the ongoing socio-economic and security challenges caused by the war in Ukraine. The authors analyze in detail the main changes that have occurred in the structure of the hotel market of the city, in particular, the reduction in the number of operating hotels, the transformation of the customer profile and the reorientation of hotel establishments to the needs of internally displaced persons, volunteers and the military. Based on data from online resources, a quantitative analysis of the types and level of service in Kharkiv hotels was carried out, the main indicators of quality, advantages and disadvantages of hotel services were determined. A separate section presents a comparative description of five Kharkiv hotels of different levels, which allows us to assess the overall level of adaptation of the industry to wartime conditions. The authors emphasize the importance of strategic planning for the further development of the hotel business in the region, in particular through attracting investment, developing domestic tourism, supporting international partnerships and reforming the security policy in the hospitality sector. The work has a practical orientation and can be useful for representatives of the tourism business, analysts, investors and local authorities in the formation of policies for the restoration and development of the tourist infrastructure of the city. The article also emphasizes the importance of using crisis conditions as an opportunity to modernize the hotel service, improve business models and actively form new formats of interaction with customers in the post-war recovery of the Ukrainian economy.
Keywords: hotel industry; Kharkiv; martial law; development; restoration